2021
DOI: 10.3390/antiox10050732
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter, an Intrauterine Toxin Affecting Foetal Development and Beyond

Abstract: Air pollution is the 9th cause of the overall disease burden globally. The solid component in the polluted air, particulate matters (PMs) with a diameter of 2.5 μm or smaller (PM2.5) possess a significant health risk to several organ systems. PM2.5 has also been shown to cross the blood–placental barrier and circulate in foetal blood. Therefore, it is considered an intrauterine environmental toxin. Exposure to PM2.5 during the perinatal period, when the foetus is particularly susceptible to developmental defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 109 publications
(164 reference statements)
0
12
0
Order By: Relevance
“…Among the environmental factors, the proinflammatory effects of air pollutants have been reported to be associated with the generation of autoimmunity and inflammation (28). As a strong oxidant and an intrauterine toxin, prenatal exposure to particulate matter was associated with longterm complications in the offspring, including impaired neonatal lung function, immune function disorders, and abnormal organogenesis (8). Ambient air pollution has been suspected to trigger autoimmune disease (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the environmental factors, the proinflammatory effects of air pollutants have been reported to be associated with the generation of autoimmunity and inflammation (28). As a strong oxidant and an intrauterine toxin, prenatal exposure to particulate matter was associated with longterm complications in the offspring, including impaired neonatal lung function, immune function disorders, and abnormal organogenesis (8). Ambient air pollution has been suspected to trigger autoimmune disease (29).…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution is reported to be associated with stimulation of oxidative stress, induction of inflammation and onset of autoimmune diseases (6,7). Prenatal air pollution exposure, as an intrauterine toxin and a strong oxidant, is associated with poor pregnancy outcomes and long-term health effects in the offsprings (8). Epidemiological studies have also revealed prenatal exposure to air pollution as a risk factor for small for gestational age, preterm birth, impaired newborn lung, impaired immune function, brain developmental disorders, and cognitive disorders after birth (9-12).…”
Section: Introductionmentioning
confidence: 99%
“…The fetal origins of adult disease hypothesis proposes that the in utero environment is critical for determining an individual’s susceptibility to certain chronic diseases later in life ( Barker, 1990 ). Notably, suboptimal nutritional status, such as undernutrition due to maternal smoking or maternal exposure to heavily polluted air, as well as toxins inhaled or ingested by pregnant mothers, play key roles in fetal underdevelopment and organ dysfunction after birth ( Wang et al, 2020 ; Chen et al, 2021 ; Li et al, 2021 ). The latent and persistent effects of fetal programming may arise from epigenetic modifications that permanently change key regulators of a range of biological processes, including cellular metabolism (e.g., mitochondrial function) and immune responses (e.g., heightened pro-inflammatory mediator production) with or without additional external environmental stimuli after birth ( Barker and Osmond, 1986 ; Petronis, 2010 ; Li et al, 2018 ; Wang et al, 2020 ; Chen et al, 2021 ).…”
Section: Pregnancy and The Development And/or Severity Of Asthma In O...mentioning
confidence: 99%
“…Maternal exposure to air pollution is associated with epigenetic alterations in the placenta and cord blood [21][22][23]. In addition, maternal PM exposure is linked to offspring with low birth weight, increased incidence of preterm birth, and increased risk of developmental disorders [24].…”
Section: Introductionmentioning
confidence: 99%